Peranan Kelompok Usaha Tanaman Hias terhadap Program Ruang Terbuka Hijau (RTH) di Kota Kendari - Agustono Slamet; R. Marsuki Iswandi; La Ode Alwi (Universitas Halu Oleo, 2019)
Ornamental Plants Business Group has an important position in the effort to reforest the city. As a producer of ornamental plant seeds, the research group provides seeds according to consumer needs. The objectives of this study are: to know the ornamental plant management system by ornamental plant business groups, and to know the role of ornamental plant business groups on Green Open Space programs.. The study was conducted in Kendari City, Southeast Sulawesi Province. Respondents were determined by 60 percent of the population of 80 people, and 6 people were taken randomly from each group. The data obtained were analyzed using descriptive methods. The results of the analysis illustrate that the management of the ornamental plant business group is carried out by dividing the tasks for group members, namely as seed gauges, sellers and workers. The role of the ornamental plant business group is more dominant in the high category, both the role of the group as a learning unit, unit, cooperation and production unit. Keywords: business group; ornamental plants; green open space